2006
DOI: 10.1103/physrevlett.96.178301
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Surfactant-Driven Fracture of Particle Rafts

Abstract: We investigate the dynamic fracture of a close-packed monolayer of particles, or particle raft, floating at a liquid-gas interface induced by the localised addition of surfactant. Unusually for a two-dimensional solid, our experiments show that the speed of crack propagation here is not affected by the elastic properties of the raft. Instead it is controlled by the rate at which surfactant is advected to the crack tip by means of the induced Marangoni flows. Further, the velocity of propagation is not constant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 13 publications
3
38
0
Order By: Relevance
“…In addition, prior studies of viscoelastic substrates have focused on substrate breakup or fracture when subjected to stresses [10,11,12,13]. Here, we observe a failure of the gel driven by surface tension.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…In addition, prior studies of viscoelastic substrates have focused on substrate breakup or fracture when subjected to stresses [10,11,12,13]. Here, we observe a failure of the gel driven by surface tension.…”
mentioning
confidence: 50%
“…Intriguingly, recent work on the surfactantinduced fracture of a particle raft [12], saw a multi-armed morphology similar to the starbursts observed here and t 3/4 spreading behavior, which the authors associated with liquid-on-liquid behavior.…”
mentioning
confidence: 97%
“…Vella et al [35] observed that adding surfactant could disrupt particle layers attached to planar water surfaces. They examined densely packed monolayers of polymeric particles ( r p = 50 μm) on the surfaces of water-glycerol solutions.…”
Section: Detaching Particles From Fluid Interfacesmentioning
confidence: 99%
“…They used a needle to inject a drop of non-ionic surfactant (polyoxyethylene sorbitan monoleate) into the layer. Providing the particles were not jammed together, Vella et al [35] observed a crack form, where the needle touched the particles, and propagate through the monolayer. They argued that localised reduction of the surface tension caused tensile stress in the particle layer, forcing the particles to rearrange [35].…”
Section: Detaching Particles From Fluid Interfacesmentioning
confidence: 99%
“…This process occurs mainly at the atomic scale near the crack tip, where the energy focuses, but also at much larger scale for particle rafts [21]. Nevertheless, macroscopic parameters, like work of fracture γ or fracture toughness K, can be defined (and measured) to describe the progression of cracks when the material properties are uniform without necessarily resorting to microscopic analysis [1,22,23].…”
Section: Introductionmentioning
confidence: 99%